Bencana Kabut Asap: Pandangan dan Sikap Non Govermental Organization - Made Selly Dwi Suryanti (Frequency of International Relations (FETRIAN), 2022)
This studi aims to expose framing in Social Movement from two Non-Governmental Organization (NGO) in facing haze disater in Indonesia that happens in Sumatera and Kalimantan. Method uses is qualitative descriptive by collecting data from book literatures, news and online news as secondary data. The result shows that each NGO has different thought about smog disaster. Greenpeace tends to view the haze disaster from the ecologys aspect; smog disaster as a product of deforestation that should be handle by Government. Meanwhile, Wahana Lingkungan Hidup (Walhi) tends to view haze disaster will affect to the social community. In the other hand, World Wide Fund (WWF) and Borneo Orangutan Survival tends to view haze disaster from different perspective that is non human species. Although each NGO has different position in order to view haze disaster, those NGO are connected to two activities form, that are campaign and advocacy. For example, campaign, will invite society to join in the protect paradise movement. While in advocacy, Greenpeace, Walhi and WWF urged and supported the Government of Indonesia to find the perpetrators of the forest fires that ended up in the haze disaster.